A Rise in Humanity Opening lecture of the academic year 2021-2022 - Sarr, Felwine (eCahiers de l'Institut, 2021)
The ePaper presents A Rise in Humanity, the opening lecture of the academic year 2021-2022 delivered by Felwine Sarr at the Graduate Institute of International and Development Studies in Geneva. In his lecture, Mr Sarr explains how societies need to take ownership of their present and future, and proposes paths to reengage at a collective level in order to fill them with meaning. The lecture is preceded by a think piece in which Marie-Laure Salles, Director of the Graduate Institute, urges us to collectively work towards the re-enchanting of our humanity - the categorical imperative of our times. It is followed by an interview in which Felwine Sarr shares his thoughts with two young researchers on how to rethink the economy.